The Role of Artificial Intelligence in Chronic Illness Care: Navigating Challenges in Clinical Nursing Practice - Sumarno Adi Subrata (Pacific Rim International Journal of Nursing Research, 2025)
Artificial intelligence (AI) is reshaping chronic illness care by providing precise, data-driven insights and fostering proactive management strategies that have the potential to enhance patient outcomes. However, integrating artificial intelligence into clinical nursing practice presents distinct challenges requiring thoughtful navigation to fully realize its benefits. AI tools promise to improve patient monitoring and enable personalized care plans while optimizing nursing workflows. Yet, as nurses work on the front lines of implementing AI, they encounter ethical, practical, and technical challenges, including data privacy and security concerns, balancing patient expectations with technological capabilities, and addressing algorithmic biases that could compromise equitable care. Nurses are crucial in ensuring that AI applications remain patient-centered, advocating for tools that genuinely reflect the diverse needs of patients with chronic illnesses. Maintaining clinical judgment amidst AI-driven recommendations requires careful consideration, as automated insights must be weighed against individualized care needs. This dynamic underscores the need to empower nurses through interdisciplinary collaboration with data scientists, continuous professional development, and resources that support them in managing potential workflow demands increased by AI tools. Moreover, fostering an adaptive, learning-oriented nursing culture is essential to embrace AI’s evolving role in healthcare. Addressing these challenges can harness AI’s full potential to improve patient care and quality of life for individuals managing chronic conditions. Supporting nurses in leading AI adoption will be instrumental in transforming chronic illness care and achieving better long-term outcomes for patients.